Regulatory Sandbox in Perspective Economic Analysis of Law - Citra Cahyaning; Budi Santoso; Nabitatus Sa'adah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Development digital economy which is characterized by rapid innovation technology finance demand framework adaptive and responsive regulation to market dynamics . One of the the approach used For bridge need innovation and certainty law is regulatory sandbox , namely trial mechanism limited for products , services , and business models innovative in regulatory oversight . This article analyze regulatory sandbox in perspective Economic Analysis of Law (EAL) as developed by Richard Posner, with emphasize the principle value , utility , and efficiency . Through approach enriched juridical- normative with analysis economics , studies This show that regulatory sandbox functioning as instrument capable regulations lower cost transactions , reducing uncertainty law , as well as support taking policy based evidence . This study also compared practice regulatory sandbox in Indonesia with several other countries, such as England , Singapore, and South Korea, for evaluate impact empirically to innovation , licensing , and welfare economics . Study results confirm that although Still face challenge implementation , regulatory sandbox still relevant as instrument efficient and progressive policies . With proper design , mechanism This potential implemented in a way cross sector as means For building governance inclusive , adaptive , and welfare - oriented innovation public .